Improving the Accessibility of the West Java Southern Area through Collector Road Widening - Maulana, Andrean; Farda, Muhammad (http://dx.doi.org/10.31427/IJSTT.2020.3.1.1, 2020)
This study assesses the impact of the road segment widening in the southern area of West Java Island. The resulting network performance is measured by volume capacity ratio, network average speed, aggregate travel distance and time. The network 4-step modeling approach was used for the analysis and data on traffic counts and average speed are used to validate the model. The study proceeds two scenarios for the analysis, namely the do-nothing scenario, in which no road widening occurs, and the do-something scenario where the road widening is carried out. The result shows that widening the road segments will contribute to improving accessibility in the area, which is reflected by lower volume capacity ratio and higher average network speed. This study also triggers a research question on alternative transport modes to improve accessibility in the southern area of West Java.